Novel ABCC8 (SUR1) Gene Mutations in Asian Indian Children with Congenital Hyperinsulinemic Hypoglycemia. (September 2014) - Jahnavi, Suresh; Poovazhagi, Varadarajan; Kanthimathi, Sekar; Balamurugan, Kandasamy; Bodhini, Dhanasekaran; Yadav, Jaivinder; Jain, Vandana; Khadgawat, Rajesh; Sikdar, Mahuya; Bhavatharini, Ayurchelvan; Das, Ashok Kumar; Kaur, Tanvir; et al.
Summary Congenital hyperinsulinemic hypoglycemia (HI) is a heterogeneous genetic disorder of insulin secretion characterized by persistent hypoglycemia, most commonly associated with inactivating mutations of the β‐cell ATP‐sensitive K+ channel (KATP channel) genes ABCC8 (encoding SUR1) and KCNJ11(encoding Kir6.2). This study aimed to screen the mutations in the genes associated with congenital HI in Asian Indian children. Recessive mutations of these genes cause hyperinsulinism that is unresponsive to treatment with channel agonists like diazoxide. Dominant KATP mutations have been associated with diazoxide‐responsive disease. The KCNJ11, ABCC8, GCK, HNF4A, and GLUD1 genes were analyzed by sequence analysis in 22 children with congenital HI. We found 10 novel mutations (c.1delA, c.61delG, c.267delT, c.619–629delCCCGAGGACCT, Gln444*, Leu724Pro, Ala847Thr, Trp898*, IVS30–2A>C, and Leu1454Arg) and two known mutations (Gly111Arg and Arg598*) in the ABCC8 gene. This study describes novel and known ABCC8 gene mutations in children with congenital HI. This is the first large genetic screening study on HI in India and our results will help clinicians in providing optimal treatment for patients with hyperinsulinemia and in assisting affected families with genetic counseling.